Pythagorean Vague b-Open Sets between Pythagorean Vague Topological Spaces - F. Nirmala Irudayam, S.Vinnarasi (Mathematical Statistician and Engineering Applications, 2022)
In this paper we devoted to study a new class of Pythagorean vague b-open sets between Pythagorean vague topological spaces. And we also contribute to study several properties of Pythagorean vague b-open sets and also discussed various relationship between Pythagorean vague semi closure and Pythagorean vague pre closure are presented.